2006
DOI: 10.2310/7010.2006.00051
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sedation With Propofol in Patients With Rett Syndrome

Abstract: Herein we present the largest retrospective case-control series of deep sedation in patients with Rett syndrome, including discussion of the unique aspects of Rett syndrome that make these patients at high risk of sedation. Twenty-one patients with Rett syndrome and 21 control patients who received propofol for deep sedation to facilitate lumbar puncture were compared. Patients with Rett syndrome required significantly less propofol than control patients when standardized for weight and the duration of the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although feasible ( Leone et al, 2012), such interventions are invasive and can have serious, and sometimes lethal, consequences for the patients (Worgall et al, 2008). In addition, Rett patients are known to display a higher risk of complications after sedation (Tofil et al, 2006), which would further complicate any surgical procedure. Based on these considerations, and in keeping with translational goals, we elected the use of an intravascular approach, which is less invasive and made possible through the use of an AAV virus able to cross the BBB (Duque et al, 2009;Foust et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although feasible ( Leone et al, 2012), such interventions are invasive and can have serious, and sometimes lethal, consequences for the patients (Worgall et al, 2008). In addition, Rett patients are known to display a higher risk of complications after sedation (Tofil et al, 2006), which would further complicate any surgical procedure. Based on these considerations, and in keeping with translational goals, we elected the use of an intravascular approach, which is less invasive and made possible through the use of an AAV virus able to cross the BBB (Duque et al, 2009;Foust et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence and case reports exist describing the sensitivity of patients with Rett syndrome to opioids and benzodiazepines and delayed recovery from anesthesia. 11 -17 Tofil et al 17 showed that individuals with Rett syndrome require lower doses of propofol and take longer to breathe independently after propofol exposure. The breathing irregularities described above, combined with sensitivities to analgesics that suppress the respiratory drive, may lead to longer intensive care unit stays and increased respiratory infection rates.…”
mentioning
confidence: 99%
“…Coordination of care following the out-patient dental exam required the collaboration of multiple teams outside of the clinic. Deep sedation for patients with RTT is considered high-risk due to many unique features of RTT, which include episodic hyperventilation, breath holding, bloating and autonomic dysfunction [ 16 ]. The family’s primary language and limited medical insurance and lack of dental insurance were key factors in the decision process for coordinating care.…”
Section: Case Presentationmentioning
confidence: 99%